Workplace health and safety, social support, and turnover intention in Private Higher Education Institutions in the Philippines - Camlian, May Maeh; Baron, Jomarie V. (Annals of Human Resource Management Research, 2025)
Purpose: This study examined workplace health and safety, social support, and turnover intention among faculty members in private higher education institutions in Region XII. This study aimed to assess these factors and their influence on faculty retention. Research Methodology: A descriptive quantitative research design was employed. Data were collected using a researcher-made questionnaire that was validated and pilot-tested for reliability. The study involved 324 full-time faculty members from 20 private higher education institutions who were selected through stratified random sampling. Results: The findings revealed that workplace health and safety practices, social support, and turnover intention play significant roles in faculty retention. Specifically, institutions have high workplace health and safety levels and social support. However, turnover intention was reported to be low across the sample. Social support, particularly belonging support, was rated the highest, whereas turnover intention across various factors remained low. Limitations: This study was limited to private higher education institutions in Region XII, and the results may not be generalizable to other regions or types of educational institutions. Additionally, self-reporting could have introduced bias. Contribution: This study contributes to the understanding of the dynamics of faculty retention in private higher education institutions, highlighting key factors such as health, safety, and social support. Novelty: This research adds novel insights by focusing on the contextualized factors influencing faculty retention in Region XII, an area underrepresented in the existing literature.